2019
DOI: 10.1097/md.0000000000014211
|View full text |Cite
|
Sign up to set email alerts
|

Liver heterotopia associated with congenital diaphragmatic hernia

Abstract: Rationale:Liver heterotopia associated with congenital diaphragmatic hernia (CDH) is a rare condition; to the best of our knowledge, only 17 cases have been reported to date. The histogenesis and clinicopathological features are largely unknown. We herein report 2 cases of liver heterotopia associated with CDH along with 17 cases described in the literature to shed light on their clinicopathological characteristics.Patient concerns:Case 1 was a vaginally delivered male newborn who presented with respiratory di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Secondly, knowledge of this association is helpful intra operatively to delineate the anatomy and facilitate the proper surgical repair of the diaphragmatic defect. Third, ectopic liver lobe may be complicated by secondary pathological condition such as torsion, infarction, and bleeding [16]. While these complications were not reported in this case, it is essential for the surgeon to be aware of these Risks.…”
Section: Discussionmentioning
confidence: 80%
“…Secondly, knowledge of this association is helpful intra operatively to delineate the anatomy and facilitate the proper surgical repair of the diaphragmatic defect. Third, ectopic liver lobe may be complicated by secondary pathological condition such as torsion, infarction, and bleeding [16]. While these complications were not reported in this case, it is essential for the surgeon to be aware of these Risks.…”
Section: Discussionmentioning
confidence: 80%
“…An interesting, different concept of liver presence in thoracic cavity is the hepatic heterotopia, classified into four types. The literature suggested some types are associated with CDHs, such as small, accessory liver lobe connected with the main liver, an isolated ectopic liver forming a macroscopic nodule and a microscopic, ectopic liver tissue [ 7 , 8 ]. It has been reported that hepatic heterotopia in the diaphragm may lead to CDH recurrence [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Normal development of the diaphragm occurs during the fifth and seventh week of gestation by the fusion of the mesenchymal septum transversum and the pleuroperitoneal folds (PPF) [ 25 ]. Key factors for the proper fusion of the PPF are the muscle progenitors which migrate from the somites into the PPF as well as the projection of the phrenic nerve from the C3–C5 segment into the PPF [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a literature review published in 2019, Mito et al reported no more than 19 cases of liver heterotopia associated with CDH. It is noteworthy that of the 19 described cases, none coincided with tumorization [ 25 ]. Neither article discussed an embryogenetic connection of CDH and ectopic liver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation